The effects of prior high intensity double poling on subsequent diagonal stride skiing characteristics - Björklund, G.; Holmberg, H. C.; Stöggl, T. (SpringerPlus, 2015)
To investigate the influence of prior high intensity double poling (DP) on physiological and biomechanical responses during subsequent diagonal stride (DIA). Methods: Eight well-trained male cross-country skiers (age 22 ± 3 yr; VO2max 69 ± 3 ml · kg-1 · min-1) roller-skied on a treadmill sequentially for 3 min at 90% DIA VO2max (DIA1), 3 min at 90% DP VO2peak and 3 min at 90% DIA VO2max (DIA2). Cardio-respiratory responses were monitored continuously and gases and metabolites in blood from the a. femoralis, v. femoralis and v. subclavia determined. Pole and plantar forces and EMG from 6 lower- and upper-body muscles were measured. Results: VO2 decreased from DIA1 to DP and increased again to DIA2 (both P < 0.05), with no difference between the DIA sessions. Blood lactate rose from DIA1 to DP to DIA2. O2 extraction was attenuated during DP (P < 0.05), but was the same during DIA1 and DIA2. EMGRMS for arm muscles during poling phase, as well as peak pole force and cycle rate were higher, while leg muscle activity was lower during DP than both sessions of DIA (all P < 0.05). The ratio of upper-/whole-body EMGRMS correlated negatively with O2 extraction in the arms during both sessions of DIA (P < 0.05). Conclusions: In well-trained skiers skiing at high-intensity DP prior to DIA did not influence VO2, muscle activation or forces in the latter. At race intensity DP does not influence the distribution of work between upper- and lower-body during a subsequent bout of DIA. O2 extraction is coupled to technical skills during skiing.